Kontribusi Kepatuhan terhadap Regulasi Syariah dalam Memperkuat Stabilitas dan Pertumbuhan Keuangan Lembaga Perbankan Syariah - Karyanto, Rania Annisa' (Maliki Interdisciplinary Journal, 2025)
Compliance with sharia principles has an important role in maintaining stability and encouraging the financial growth of sharia banking in Indonesia. Implemented sharia values ​​not only strengthen fair and transparent governance, but also contribute to more effective risk management. Consistency in implementing this compliance encourages increased customer trust, strengthens loyalty, and creates a sustainable financing system. Apart from that, sharia compliance is also a competitive advantage that differentiates sharia banks amidst the competitive financial industry. To maintain the relevance and effectiveness of sharia compliance, it is necessary to strengthen the role of the Sharia Supervisory Board, use technology that is in accordance with sharia principles, and increase public understanding of the sharia financial system. This research confirms that the integration of sharia values ​​in bank operations is the key to creating quality and sustainable growth.